Hybrid vehicles are worth it! [paper discussion and authors' reply]. (IEEE spectrum)
In March, IEEE Spectrum published an article examining the case for the hybrid-electric vehicle from an economic perspective [?Are hybrid vehicles worth it??, L.B. Lave et al., see ibid., p. 47-50, 2001]. It concluded that hybrids were not economically worthwhile. Reader response to the piece was strong and almost universally negative. In furtherance of the goal of presenting both sides of the argument, this paper consists of a representative selection of the letters IEEE Spectrum received in response, along with a reply from the original authors